Sensor-less force-reflecting macro–micro telemanipulation systems by piezoelectric actuators - Amini, H.; Farzaneh, B.; Azimifar, F.; Sarhan, A.A.D. (Elsevier, 2016)
This paper establishes a novel control strategy for a nonlinear bilateral macro–micro teleoperation system with time delay. Besides position and velocity signals, force signals are additionally utilized in the control scheme. This modification significantly improves the poor transparency during contact with the environment. To eliminate external force measurement, a force estimation algorithm is proposed for the master and slave robots. The closed loop stability of the nonlinear micro–micro teleoperation system with the proposed control scheme is investigated employing the Lyapunov theory. Consequently, the experimental results verify the efficiency of the new control scheme in free motion and during collision between the slave robot and the environment of slave robot with environment, and the efficiency of the force estimation algorithm.